Juridical Study of the Practice of Fishing Using Explosives (A Case Study of Fishermen on Semau Island - Herli Paulus Poto; Jimmy Pello; Bhisa Vitus Wilhelmus (Fakultas Hukum Dehasen, 2026)
The practice of fishing using explosives is a form of destructive fishing that not only violates fisheries law but also causes serious impacts on the sustainability of marine ecosystems and the socio-economic life of coastal communities. Although it has been strictly regulated under Law Number 45 of 2009 concerning Fisheries and reinforced by the Minister of Marine Affairs and Fisheries Regulation Number 36 of 2023, this illegal practice continues to occur in several coastal areas, including Semau Island, Kupang Regency, East Nusa Tenggara Province. This study aims to analyze the factors that cause fishermen on Semau Island to continue using explosives in fishing activities despite legal prohibitions, and to examine the juridical impacts on perpetrators, communities, and marine ecosystems. This research employs an empirical legal research method with a case study approach. Data were obtained through interviews with fishermen, law enforcement officers from the Marine and Air Police Directorate (Ditpolairud), and other related stakeholders. These data were supported by document studies of legislation, court decisions, and relevant legal literature. The data were analyzed using a descriptive qualitative approach based on theories of law enforcement, legal certainty, criminal liability, and legal awareness. The findings reveal several key factors encouraging fishermen to continue using explosives, including economic pressure and livelihood needs, time efficiency with larger catches, easy access to explosive materials, long-standing fishing traditions, low levels of legal awareness and compliance, and limited alternative livelihoods. Furthermore, the practice results in juridical consequences in the form of criminal sanctions for offenders, socio-economic losses for coastal communities, and severe damage to marine ecosystems, particularly coral reefs and fish resources. In addition, weak law enforcement and the limited deterrent effect of court decisions have reduced the effectiveness of legal implementation in practice. This study concludes that a gap still exists between legal norms and their practical implementation in fishing activities on Semau Island. Therefore, stronger law enforcement, increased legal awareness among fishermen, and integrated policies addressing legal, social, economic, and environmental aspects are necessary to achieve sustainable and equitable fisheries resource management.